Physical Culture in the Formation of a Highly Moral Personality (Eurasian Journal of Learning and Academic Teaching, 2022)
Recently, sport has become an increasingly popular activity among people, but few people know about its main features. So the main purpose of this work is to show how this sphere of human activity can affect not only the physical health of a person, but also the formation of a highly moral personality